iTutorGroup: A case study of covert native-speakerism underneath a social justice façade - Alvarez, Hector Sebastian (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2022)
This article examines the covert native-speakerist strategies iTutorGroup utilizes to discriminate against teachers of nationalities the company appears to deem as undesired. Through content analysis of numerous job application submissions to iTutorGroup’s website, results show iTutorGroup’s automatic hiring process offers teachers of these nationalities a much lower potential wage and only a video-recorded asynchronous interview, if not complete refusal to an interview. In contrast, British, Australasian, and North American nationals are afforded a much higher potential wage as well as a one-on-one live interview. The company conceals these nuanced discriminatory strategies with a façade of equality since they are one of TESOL International Association’s Global Partners. As a Global Partner, iTutorGroup follows suit in pretending to uphold TESOL’s nondiscrimination policies.